Zinc-containing coating film
By adding graphene to the coating film and adjusting its added amount, the cost and environmental problems caused by high zinc content are solved, and the anticorrosion performance and better physical properties are achieved with traditional zinc-rich coatings, reducing zinc content and improving zinc content The salt spray resistance of the coating film.
Patent Information
- Application Number
- CN202410854209.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-04
- Filing Date
- 2024-06-27
- Publication Date
- 2025-01-07
AI Technical Summary
The high zinc content in existing zinc-rich coatings leads to increased costs and environmental pollution, and the corrosion resistance performance is difficult to match traditional zinc-rich coatings after the zinc content is reduced.
Add an appropriate amount of graphene to the coating film, control its addition amount to adjust the corrosion potential and conductivity, reduce the zinc content, and increase other inorganic and organic additives and fillers to ensure that the anticorrosion performance of the coating film reaches the same as that of traditional zinc-rich coatings. level.
The high corrosion resistance of the coating film after the zinc content is reduced is achieved, which reduces costs and reduces hidden dangers to human health and the environment. The coating film has a longer salt spray resistance time and has better physical properties such as toughness and adhesion.
Smart Images

Figure CN119264764A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of metal protection and zinc-containing coatings, and in particular to a zinc-containing coating film containing graphene. Background Art
[0002] In environments with high corrosion levels, such as offshore and water-based buildings, steel corrosion protection has become an important issue. In order to reduce the losses caused by metal corrosion, zinc-rich paint is often used on the surface of steel structures for corrosion protection. It is well known that the main raw material of zinc-rich paint is zinc powder, and the content of zinc powder can generally reach more than 70wt% of the total weight of the paint. Since the price of zinc powder fluctuates with the price of the international market, the continuous increase in zinc powder prices has caused the cost of zinc-rich paint to increase, which makes it difficult to control the raw material cost of the paint, which is undesirable for both paint manufacturers and users. In addition, due to the high zinc content in the paint, a large number of tiny zinc-containing particles may be formed during the paint construction, which will bring health risks to the constructors and cause pollution to the environment.
[0003] Therefore, the technical issue to be solved is how to reduce the zinc content in the coating while ensuring the anti-corrosion effect of the coating, thereby reducing the cost of the coating, reducing the adverse effects of zinc price fluctuations, and eliminating hidden dangers to human health and environmental safety.
[0004] The general solution is to reduce the zinc content in the coating while increasing the amount of other additives. However, since other additives cannot replace zinc to achieve the sacrificial anode effect, the anti-corrosion effect is often lower than expected. For example, patent 201510988687.9 uses one or more of conductive carbon black, conductive carbon fiber and graphene as functional fillers, and its corrosion resistance is characterized by salt spray resistance time. According to the embodiment, when conductive carbon black and conductive carbon fiber are used in combination as functional fillers, the salt spray resistance time reaches 1500h. Patent 201510497999.X uses graphene prepared by oxidation method and added to the anti-corrosion coating. Its salt spray resistance time is up to 1000h, which only reaches the atmospheric corrosivity level C2~C3 recorded in HG / T 5573-2019.
[0005] The current situation of zinc-containing paint is that although the amount of zinc added in the paint has been reduced, the anti-corrosion performance of the paint still cannot reach the level of zinc-rich paint, and there is still the problem of too low anti-corrosion performance and short protection time.
[0006] In view of the problems in the prior art, it is necessary to develop a zinc-containing coating having a zinc content lower than that of the existing zinc-rich coating, while its anti-corrosion performance needs to be comparable to that of the existing zinc-rich coating. Summary of the invention
[0007] In view of the above prior art, the purpose of the present invention is to provide a coating film having a lower zinc content than the existing zinc-rich coating. In this regard, the inventors found that by adding graphene to the coating film and changing the amount of graphene added to control the corrosion potential and conductivity of the coating film within a suitable range, it is possible to achieve the purpose of maintaining high corrosion resistance while reducing the zinc content in the coating film without adding functional fillers such as conductive carbon black and conductive carbon fiber, and the atmospheric corrosion level of the coating film reaches the C4-C5 level specified in HG / T 5573-2019. Due to the addition of an appropriate amount of graphene, the low-zinc coating film has performance comparable to the common zinc-rich coating films on the market, including anti-corrosion performance and basic physical properties of the coating film.
[0008] The coating film contains resin, zinc and graphene. On the premise of ensuring that zinc and graphene are fully dispersed in the coating film, other inorganic and organic additives and fillers can be added to the coating film to ensure that the coating film is easy to use and construct.
[0009] The zinc in the coating has a lower potential than iron, so it plays a cathodic protection role for easily oxidized metals such as iron. Generally, spherical zinc powder particles are used, and the particle size is less than 20 microns, preferably less than 10 microns. Compared with the traditional zinc-rich coating, the zinc content in the coating of the present invention is lower, which is less than 60wt% of the coating mass, and at the same time, it is more than 30wt% to ensure that the coating maintains a suitable corrosion potential. In order to ensure the cathodic protection effect in the coating, the zinc content is preferably more than 40wt% and less than 60wt%. When the zinc content is less than 30wt%, the zinc particles in the coating are too far away from each other and cannot form the conditions for cathodic protection. At this time, even if graphene is added, it is difficult to improve the contact between the zinc particles, so the anti-corrosion performance of the coating is not ideal. The zinc content in the coating can be measured by referring to the method recorded in the industry standard HG / T 3668-2020 zinc-rich primer Appendix A Determination of the content of metallic zinc in non-volatile matter (differential scanning calorimetry) or Appendix B Determination of the content of metallic zinc in non-volatile matter (chemical analysis method).
[0010] The coating film also contains an appropriate amount of graphene. Since graphene is conductive, the graphene evenly distributed in the coating film can improve the utilization efficiency of zinc powder during the corrosion process by connecting zinc powder particles, thereby improving the anti-corrosion effect of the coating film. At the same time, the addition of graphene also provides the coating film with better basic physical properties, such as toughness, impact resistance, adhesion, etc. The graphene content in the coating film is more than 0.01wt% and less than 0.5wt%, preferably more than 0.05wt% and less than 0.15wt%. When the graphene content in the coating film is too low, the effect of graphene will not be reflected. If the content of graphene is too high, the performance of the coating film cannot be greatly improved in the same proportion, and the cost of the coating film itself will also increase. When the graphene content is higher than 0.5wt%, the viscosity of the coating increases or gelation occurs, affecting the construction performance of the coating. At this time, if a solvent is added to reduce the viscosity of the coating, VOC will exceed the standard. There is no particular restriction on the type of graphene, and graphene prepared by mechanical exfoliation, graphene exfoliated by chemical intercalation, or chemically oxidized and reduced graphene may be used.
[0011] The corrosion potential range of the coating film with the above composition is above -1.10V and below -0.70V, and the conductivity is above 0.00001S / cm and below 0.1S / cm. The coating film here refers to a dry film obtained by drying a wet film prepared on an iron plate for 7 days. By adjusting the thickness of the wet film, the thickness of the dry film is ensured to be 50 microns. When measuring the conductivity of the coating film, in order to avoid the influence of the iron plate on the conductive properties of the coating film, it is necessary to remove the substrate such as the iron plate under the coating film. If the coating film is used as a primer, in order to determine the conductivity of the above coating film, it is necessary to remove the upper intermediate paint and topcoat first, and then measure the conductivity of the primer. The conductivity is measured within 1 day of obtaining the dry film. The corrosion potential is measured on the 8th day after the dry film is obtained. Through research, we found that the corrosion potential and conductivity of the coating film should be kept within a suitable range to obtain an ideal anti-corrosion effect, which is specifically reflected in the extension of the salt spray resistance time. The corrosion potential of the coating is controlled within a suitable range to ensure that the zinc particles in the zinc-containing coating can play their sacrificial anode role. The corrosion potential of the coating is preferably above -1.10V and below -0.90V. If the conductivity of the coating is too low, it means that its conductivity is poor, and a good conductive path cannot be formed in the coating, which easily causes some zinc particles to be isolated from each other in the coating and cannot be fully utilized. This explains why, although there are still a large number of zinc particles in the coating, the anti-corrosion performance of the coating has failed, which is a phenomenon that often occurs in the field of anti-corrosion coatings. On the other hand, if the conductivity of the coating is too high, it may cause the zinc in the coating to be consumed too quickly. Although it can show good anti-corrosion performance in a short time, it reduces the long-term protection effect of the coating on the substrate. Our research found that in order to balance the synergistic effect of the corrosion potential and conductivity of the coating, the preferred range of the conductivity of the coating is above 0.0001S / cm and below 0.01S / cm. The conductivity of the coating is further preferably above 0.001S / cm and below 0.01S / cm. The corrosion potential of the coating can be tested and calculated by the electrochemical polarization potential test method, while the conductivity of the coating can be measured by the four-probe method.
[0012] The graphene in the coating of the present invention has a suitable degree of oxidation, and the atomic ratio of oxygen to carbon measured by X-ray photoelectron spectroscopy, i.e., the O / C ratio, is preferably greater than 0.001 and less than 0.500. When the O / C ratio is controlled to be above 0.001, the graphene is more easily evenly dispersed in the coating, so that the coating obtains higher barrier properties, which is reflected in the decrease in the transmittance of the coating to water, oxygen, etc., and it is further preferred that the O / C ratio is greater than 0.050. At the same time, if the oxygen content is too high, the conductivity of graphene may decrease, so the O / C ratio is preferably less than 0.500. In order to enable graphene to obtain a more suitable conductivity, thereby ensuring that it can provide appropriate conductivity when used in the coating, the O / C ratio of graphene is more preferably less than 0.340. The method for extracting graphene from coatings can refer to the method mentioned in Appendix A of the industry standard HG / T 5573-2019, Graphene material qualitative analysis (scanning electron microscope energy spectrum method), and the graphene is extracted by high-speed centrifugation and measured by X-ray photoelectron spectroscopy (XPS). The C1s main peak based on carbon atoms is 284.3eV, and the O1s peak based on oxygen atoms belongs to the peak near 533eV. The O / C ratio is calculated from the area ratio of each peak, retaining three decimal places.
[0013] The graphene in the coating of the present invention has a suitable degree of surface treatment. Since the surface treatment agent contains nitrogen, the atomic ratio of nitrogen to carbon in the above-mentioned graphene measured by X-ray photoelectron spectroscopy, i.e., N / C, is preferably 0.001 or more and 0.090 or less. Suitable N / C ratio means that the surface treatment degree of graphene is within a suitable range, and accordingly, the adhesion of graphene to the resin in the coating is better, and the basic physical properties of the coating can be maintained or even improved. Therefore, the range of the N / C ratio is further preferably 0.003 or more and 0.030 or less. The N / C ratio of graphene can be easily adjusted in the above range by, for example, the amount of attachment of the following amino aryl compound on graphene. Graphene can be extracted from the coating composition with reference to the method of Appendix A of HG / T5573-2019, and the N / C ratio of graphene is determined by X-ray photoelectron spectroscopy (XPS). The main peak of C1s based on carbon atoms is 284.3 eV, and the peak of N1s based on nitrogen atoms is attributed to a peak near 402 eV. The N / C ratio is calculated from the area ratio of each peak, retaining three decimal places.
[0014] The size of the graphene in the coating of the present invention in the direction parallel to the graphene layer is preferably greater than 0.10 μm and less than 100 μm. This size refers to the arithmetic mean of the maximum diameter and the minimum diameter of the graphene sheet on the plane parallel to the graphene sheet layer. Considering the barrier properties of graphene to water, oxygen, etc. in the coating, and the formation of a conductive network sufficient to connect zinc particles in the coating, the above-mentioned size of the graphene used in the present invention is more preferably greater than 10 μm. On the other hand, in order to improve its dispersion in the coating and improve the basic properties of the coating such as corrosion resistance and adhesion, the above-mentioned size of the graphene is more preferably less than 50 μm. Here, the size of graphene in the coating composition in the direction parallel to the graphene layer can be measured by the following method, that is, graphene is extracted from the coating composition and observed with an electron microscope. In order to accurately include graphene in the field of view, the magnification is enlarged to 1500-50000 times for observation. For 10 randomly selected graphenes, the longest length (long diameter) and the shortest length (short diameter) in the direction parallel to the graphene layer are measured respectively, and the arithmetic mean of (long diameter + short diameter) / 2 is calculated. The method for extracting graphene in the coating can refer to the method mentioned in the qualitative characterization of graphene materials (scanning electron microscope energy spectrum method) of Appendix A of the industry standard HG / T 5573-2019, and the graphene is extracted by high-speed centrifugation, and placed on a copper tape and placed in a scanning electron microscope to observe and measure the size of graphene. Since the thickness of graphene is only at the nanometer level, and the size in the plane direction is at the micrometer level, a laser particle size analyzer can also be used to more conveniently characterize and measure the size of graphene in the direction parallel to the graphene layer. In addition, by miniaturizing graphene oxide or reduced graphene by the method described below, the size of graphene in the direction parallel to the graphene layer can be easily adjusted within the above range. In addition, commercially available graphene oxide or graphene of an appropriate size can also be used.
[0015] The average thickness of graphene is preferably 0.3 nm or more and 300 nm or less. The average thickness of graphene of 0.3 nm is the theoretical minimum value of graphene, indicating a single layer of graphene. On the other hand, by making the average thickness of graphene less than 300 nm, it will be easy to obtain high dispersibility in the composition, and it will be easy to obtain corrosion resistance and high adhesion. From the perspective of uniform dispersion in the resin and improving corrosion resistance and adhesion, the average thickness of graphene is preferably less than 300 nm, more preferably less than 200 nm, further preferably less than 150 nm, and more preferably less than 100 nm. Here, the average thickness of graphene in the present invention can be measured by the following method, that is, graphene is extracted from the coating composition and observed with an atomic force microscope. In order to accurately observe graphene, the field of view is expanded to 1 to 20 μm square, and the thickness of 10 randomly selected graphenes is measured respectively, and the arithmetic mean thereof is calculated. Furthermore, the thickness of each piece of graphene is the arithmetic mean of the measured values of the thickness at 5 randomly selected places on the graphene sheet.
[0016] The resin in the coating of the present invention comprises any one of epoxy resin, polyurethane resin or acrylic resin. The resin provides film-forming property of the coating, and plays a bonding role for various inorganic particles in the coating to ensure the formation of the coating. On the other hand, the resin also provides the coating with barrier properties against water, oxygen, etc. under corrosive conditions.
[0017] The graphene in the coating film of the present invention is treated with a surface treatment agent, and the surface treatment agent is the following amino aryl compound.
[0018]
[0019] Wherein, A represents an aromatic group or a heterocyclic aromatic group with a condensation number of 1 to 4, the aromatic group is composed of one of benzene, naphthalene, anthracene, phenanthrene, tetracene, and pyrene, and the heterocyclic aromatic group is composed of one of pyrrole, imidazole, pyridine, triazine, indole, quinoline, and carbazole, and R 1 , R 2 Each independently represents a hydrogen atom, a halogen atom, a carboxyl group, a hydroxyl group, a nitro group, a methyl group, an ethyl group, a propyl group or a butyl group, and R 3 A and N are directly bonded or connected by an alkylene group, wherein the carbon number of the alkylene group is an integer of 1 to 10, and R 4 , R 5 Each independently represents a hydrogen atom, a methyl group, an ethyl group, a propyl group or a butyl group.
[0020] The surface treatment agent is a compound containing both an amine group and an aromatic group. Regarding A, the aromatic group is preferably one of benzene and naphthalene, and more preferably benzene. The heterocyclic aromatic group is preferably one of pyrrole and imidazole, and more preferably pyrrole. 1, R 2 Each of R is independently selected from the group consisting of a hydrogen atom, a halogen atom, a carboxyl group, and a hydroxyl group. 3 The carbon number of the alkylene group should not be too large. If the carbon number is greater than 10, the molecular volume of the surfactant will increase, and the carbon content will also increase. This will increase the difficulty of graphene surface treatment and affect the amount of surface treatment agent attached to the graphene surface, thereby reducing the N / C ratio of graphene. In order to ensure that the O / C ratio and N / C ratio in graphene are within the above-mentioned preferred range, we found through experimental research that R is preferred here. 3 When it is an alkylene group, the number of carbon atoms is an integer of 0 to 2. 4 , R 5 Preferably, one of hydrogen atom, methyl group and ethyl group is selected independently. The surface treating agent can be selected from, but not limited to, aniline, chloroaniline, bromoaniline, iodoaniline, carboxyaniline, methylaniline, ethylaniline, butylaniline, N-methylaniline, N-ethylaniline, N-butylaniline, N-hexylaniline, N-octylaniline, N-decylaniline, dimethylaniline, diethylaniline, dibutylaniline, nitroaniline, naphthylamine, naphthylamine hydrochloride, nitronaphthylamine, N-methylnaphthylamine, N-ethylnaphthylamine, N-methylnaphthylamine hydrochloride, N, N-dimethylnaphthylamine, aminopyrrolidine, dopamine hydrochloride, 2-phenylethylamine hydrochloride, decylaminobenzene hydrochloride, hexadecylaminobenzene hydrochloride, benzylamine, 2-bromo-4-chlorobenzylamine, etc.
[0021] In the present invention, due to the addition of a suitable amount of graphene of a suitable type, the conductivity and corrosion potential of the coating with a low zinc content can be controlled within a certain range, so that the coating has a longer salt spray resistance time. At the same time, by adjusting the preparation method of the coating, it is ensured that the graphene is fully dispersed in the coating, so as to maximize the effect of the interaction between the graphene and the low content of zinc.
[0022] The preparation of the above-mentioned coating film with low zinc content containing graphene can be prepared by the following method:
[0023] (1) Mixing graphene, zinc powder and solvent for 5-15 minutes;
[0024] (2) Add resin and disperse for 15-30 minutes;
[0025] (3) Add a curing agent, mix and prepare a coating film, and dry it.
[0026] It is recommended to use a high-speed disperser for mixing and dispersing, and the speed of mixing and dispersing is preferably above 1000rpm, and preferably below 2500rpm. Increasing the dispersion speed of the disperser is conducive to the full mixing and uniform dispersion of each component. However, it should be noted that the dispersion speed is not easy to be too high, and the dispersion time should not be too long, so as to avoid over-dispersion of each component. This is because too high a dispersion speed or too long a dispersion time can easily cause the temperature of the above-mentioned mixture to be too high, which may destroy the composition or structure of each component, resulting in ineffective addition of each component, which in turn reduces the performance of the coating.
[0027] The low-zinc content coating containing graphene prepared by this method ensures sufficient contact between graphene and zinc powder. The graphene in the coating forms a conductive path of appropriate degree between zinc powder particles, which improves the utilization rate of zinc powder while avoiding excessive consumption of zinc powder. Therefore, the coating has good performance in both short-term and long-term anti-corrosion effects.
[0028] According to the present invention, due to the addition of an appropriate amount of graphene and the adjustment of the elemental composition and size of the graphene, the low-zinc coating has performance comparable to the common zinc-rich coatings currently on the market. Compared with coatings with the same zinc content, the coating of the present invention has higher conductivity, better short-term and long-term anti-corrosion effects, higher barrier properties, and lower gloss. The above beneficial effects can be achieved by characterizing the physical properties of the above coating, specifically including characterization means such as the toughness, impact resistance, gloss, adhesion, oxygen permeability, and salt spray resistance time of the coating. Compared with traditional zinc-rich coatings, the above properties of the coating of the present invention are maintained, while the zinc content in the coating is reduced to below 60wt%. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Schematic diagram of the structure of the surface-treated graphene used in Example 1. DETAILED DESCRIPTION
[0030] The present invention is further described below by way of examples, but these examples are only for illustration and do not limit the scope of the present invention.
[0031] 1. Raw materials
[0032] (1) Used for preparing graphene
[0033] Natural graphite, concentrated sulfuric acid (98%, AR), potassium permanganate (AR), sodium nitrate (AR), hydrogen peroxide (30%, AR), dilute hydrochloric acid, and sodium dithionite were purchased from Sinopharm Chemical Reagent Co., Ltd.
[0034] Deionized water (homemade).
[0035] (2) Graphene used for preparation of surface treatment
[0036] Graphene (homemade).
[0037] Surfactants: 4-chloroaniline, dopamine hydrochloride, 2-phenylethylamine hydrochloride, decanylaminobenzene hydrochloride, hexadecylaminobenzene hydrochloride were purchased from Sinopharm Chemical Reagent Co., Ltd.
[0038] Deionized water (homemade).
[0039] (3) Used in the preparation of paints and coatings:
[0040] Resin and corresponding hardener:
[0041] Epoxy resin: SM-601 epoxy resin manufactured by Sanmu Group and JT-6050 manufactured by Shanghai Jingtian New Materials Technology Co., Ltd.
[0042] Polyurethane resin: PTMG650 (polytetramethylene furan) and 4,4'-methylenebis(phenyl isocyanate) manufactured by Mitsubishi Chemical Corporation
[0043] Acrylic resin: "PARALOID" (registered trademark) B-66 manufactured by DOW Chemical Company Zinc: zinc powder purchased from Sinopharm Reagent Company.
[0044] 2. Testing equipment and methods for related performance in the embodiments and comparative examples of the present invention:
[0045] A. Determination of the size of graphene in the direction parallel to the graphene layer: Particle size distribution analyzer (Horiba LA960)
[0046] Test method: Graphene was diluted to 0.1 wt% with N-methylpyrrolidone, and treated for 60 seconds using "FILMIX" (registered trademark) 30-30 (PRIMIX) at a rotation speed of 40 m / s (shear rate: 20,000 per second). The graphene was added dropwise to the test chamber of the particle size distribution analyzer for size testing and confirmation.
[0047] B. Determination of O / C ratio and N / C ratio in graphene: X-ray photoelectron spectrometer (Shimadzu AXIS Ultra DLD)
[0048] Test method: After the reduced graphene dispersion prepared in each embodiment and comparative example was filtered with a vacuum filter, it was diluted with water to 0.5 mass % and subjected to a vacuum filtration cleaning process, which was repeated 5 times, and then freeze-dried to obtain a surface-treated graphene powder. The photoelectron spectrum of the surface-treated graphene powder obtained was measured using an X-ray photoelectron spectrometer Quantera SXM (manufactured by PHI). The X-ray light source was a monochromatic Al K α1,2The X-ray was used for the experiment (1486.6eV), the X-ray diameter was 200μm, and the grazing angle was 45°. The C1s main peak based on carbon atoms was 284.3eV, the O1s peak based on oxygen atoms was attributed to a peak near 533eV, and the N1s peak based on nitrogen atoms was attributed to a peak near 402eV. The O / C ratio was calculated by the area ratio of the O1s peak to the C1s peak, with three decimal places retained. In addition, the N / C ratio was calculated by the area ratio of the N1s peak to the C1s peak, with three decimal places retained.
[0049] C. Determination of corrosion potential of coating: Electrochemical workstation (BioLogic VSP)
[0050] Test method: Spray the above coating and dry it for 7 days to obtain a dry film, and test the corrosion potential on the 8th day after obtaining the dry film. By adjusting the thickness of the wet film, ensure that the thickness of the dry film is 50 microns. As the test electrode, use the platinum electrode as the counter electrode and the Ag / AgCl electrode as the reference electrode to connect the various electrode wires of the electrochemical workstation. The measurement mode is selected as the polarization potential measurement mode, and the voltage scanning range is set to -1.2 to -0.2V. Calculate the corrosion potential of the coating according to the polarization curve, and keep two decimal places.
[0051] D. Determination of conductivity of coating film: Four-probe resistivity meter (Mitsubishi Chemical MCP-T610)
[0052] Test method: spray the above coating and dry it for 7 days to obtain a dry film, and conduct the conductivity test on the first day of obtaining the dry film. In order to avoid the influence of the iron plate on the conductive properties of the coating, it is necessary to remove the iron plate and other substrates under the coating, and ensure that the thickness of the dry film is 50 microns. If the coating is used as a primer, in order to determine the conductivity of the above coating, it is necessary to remove the upper intermediate paint and topcoat first, and then measure the conductivity of the primer. Input the thickness of the dry coating into the measuring instrument, set the test voltage to 10V, and select the volume conductivity measurement mode. Place the probe of the resistivity meter stably on the coating and read the reading after it stabilizes for 10s. Take 5 locations evenly on each coating for measurement, and then take the average value as the conductivity of the coating, retaining two significant digits.
[0053] E. Flexibility: Bending tester (LEPU FA-YZQ-II)
[0054] Test method: Apply the paint on the iron plate. After the paint film is dry, open the bending tester completely, select shafts of different diameters, insert the sample, and make the paint face the base plate. Close the instrument at a steady speed within 1-2 seconds to bend the test plate 180° around the axis. The minimum shaft diameter that does not cause cracking of the paint film indicates the flexibility of the paint film.
[0055] F. Impact resistance: Impact tester (DALAIQCJ-120)
[0056] Test method: Place the dry paint film under the impact tester and drop a fixed-mass hammer on the test plate. The product of the maximum height that does not cause damage to the paint film and the mass of the hammer is used to express the impact resistance of the paint film.
[0057] G. Glossiness: gloss meter (SPEEDRE SDR600)
[0058] Test Method: The gloss measurement of a coating is based on the surface reflection of light relative to a polished glass reference standard. The amount of light reflected on the surface depends on the angle of incidence and the nature of the surface. Gloss is classified as low gloss, semi-gloss or high gloss. To determine the most appropriate measurement angle, start the measurement with the gloss meter set at a 90° angle of incidence. If the test result is between 10-70, the coating is called "semi-gloss" and should be measured using an angle of 60°. If the result is less than 10, the product is "low gloss" and should be measured using an angle of 85°. If greater than 70, the product is called "high gloss" and should be measured using an angle of 20°.
[0059] H. Adhesion: 100-grid knife
[0060] Test method: The coating adhesion characterization method refers to the relevant national standard GB / T 9286-2021. It is a test method to evaluate the resistance of the coating to detach from the substrate by cutting the coating with a right-angle grid pattern to penetrate the substrate. Since it is a parallel comparison test conducted under the same conditions, it reflects the adhesion of the coating on the metal substrate to a certain extent. The less the peeling of the coating observed in the test, the lower the grade. The coating with the least peeling at level 0 has the best adhesion, while the coating with the most peeling at level 5 has the worst adhesion.
[0061] I. Oxygen permeability: Gas permeation tester (Labthink CLASSIC 216)
[0062] Test method: The coating is made into a film and the gas permeability test is carried out on a gas permeation tester using the differential pressure method according to JIS K7126-A standard. The test coating film is fixed in the middle of the test chamber to separate the chamber into an upper chamber and a lower chamber with a constant pressure difference between them. The gas molecules will penetrate the sample from the high-pressure chamber into the low-pressure chamber, and then the pressure change of the low-pressure chamber is monitored and the gas transmission rate is calculated by the system.
[0063] J. Salt spray resistance: neutral salt spray test chamber (HAIDA HD-E808-120)
[0064] Test method: Prepare the coating by spraying on the sandblasted iron plate according to the national standard GB / T 1771-2007. After the coating is fully dried, scratch the surface with a scratch width of 1mm and a length of 20mm. Perform the neutral salt spray test in accordance with HG / T 5573-2020. Test continuously in the neutral salt spray test chamber, and record the test time and experimental phenomena. The time for the coating to bubble, rust, crack, peel or the unidirectional corrosion of the scratch to exceed 1.5mm is used to indicate the salt spray resistance of the coating.
[0065] K. Corrosion expansion width after 100h salt spray test: neutral salt spray test chamber (HAIDA HD-E808-120)
[0066] Test method: Spray the coating on the sandblasted iron plate according to the national standard GB / T 1771-2007. After the coating is fully dried, scratch the surface with a scratch width of 1mm and a length of 20mm. Refer to HG / T 5573-2020 for the neutral salt spray test. Perform the test in a neutral salt spray test chamber for 100h without interruption, remove the iron plate, scrape the coating near the scratch to expose the iron plate below, and measure and record the unidirectional corrosion width of the iron plate at the scratch.
[0067] L. Determination of coating agglomeration: scraper fineness meter (Tianjin Shunnuo QXD0-100)
[0068] Test method: According to GB / T1724-89, drop the mixed coating composition into the deepest groove of the scraper fineness meter, use a scraper to pull the groove from deep to shallow, so that the coating fills the groove, and read the maximum particle size of the coating composition within 5 seconds. If the maximum particle size of the coating composition is not greater than 40 microns, it means that the components in the coating are evenly dispersed and it is judged that no agglomeration occurs. If the maximum particle size of the coating composition is greater than 40 microns, it is judged that agglomeration occurs.
[0069] 3. Preparation method of graphene:
[0070] Add 220ml of 98% concentrated sulfuric acid, 3.5g of sodium nitrate, and 21g of potassium permanganate to 10g of natural graphite powder, stir the mixture in an ice bath for 1 hour, and control the temperature of the mixture at about 20°C. Take out the above mixture, react with stirring in a 35°C water bath for 4 hours; after adding 500ml of deionized water, react the obtained suspension at 90°C for 15 minutes. Finally, add 600ml of deionized water and 50ml of hydrogen peroxide, and react for 5 minutes to obtain a graphite oxide dispersion. Filter the obtained dispersion while hot, wash out the metal ions with a dilute hydrochloric acid solution, wash with deionized water to remove the acid, repeat the washing until the pH value is 7, and filter and concentrate to 45wt% of graphene oxide wet cake.
[0071] Graphene oxide of different sizes can be obtained by using graphite raw materials of different sizes.
[0072] By adjusting the addition ratio of the oxidant, the oxidation degree and the exfoliation degree of the raw graphite are adjusted, thereby controlling and adjusting the thickness of the graphene oxide.
[0073] Example 1
[0074] (Preparation of graphene treated with a surface treatment agent)
[0075] 11.1 g (5 g solid) of 45 wt% graphene oxide wet cake prepared by the above method was diluted with 988.9 g of ion exchange water to a concentration of 0.5 wt%, and treated with a 2.5-type homogenizer (PRIMIX) at a speed of 3000 rpm for 30 minutes to obtain a uniform graphene oxide dispersion. Sodium hydroxide was added to adjust the pH to 8.5, 10 g of dopamine hydrochloride was added, and treated with a 2.5-type homogenizer (PRIMIX) at a speed of 3000 rpm for 60 minutes. 25 g of sodium dithionite was added to the treated graphene oxide dispersion, and stirred at a speed of 3000 rpm for 1 hour on a 40°C water bath using a 2.5-type homogenizer (PRIMIX) and reduced. Thereafter, the graphene water wet cake was obtained by vacuum filtration, and the washing process of diluting with water to 0.5 wt% and vacuum filtration was repeated 5 times to obtain the graphene water wet cake. The obtained graphene water-wet cake was diluted with water to 1 wt% and placed in an eggplant-shaped flask. The eggplant-shaped flask was frozen with liquid nitrogen and freeze-dried overnight using a freeze dryer FDU-1200 manufactured by EYELA to obtain graphene powder. The O / C ratio, N / C ratio and the size of the graphene in the direction parallel to the graphene layer were measured using the above test method, and the results are recorded in Table 1.
[0076] (Preparation of coating film)
[0077] Weigh 50 mg of graphene powder (0.05 wt% relative to the total weight of solids) and 30 g of zinc powder, add 18 g of xylene and 2 g of n-butanol, and stir at 2500 rpm for 5 minutes using a 2.5-type homogenizer (PRIMIX). Add 14.8 g of epoxy resin main agent to the resulting solution, and stir at 2500 rpm for 15 minutes using a 2.5-type homogenizer (PRIMIX). Add 7.4 g of epoxy resin curing agent (70% solid content, 5.2 g) and stir at 1000 rpm for 5 minutes using a 2.5-type homogenizer (PRIMIX) to homogenize, and prepare a coating composition.
[0078] After filtering the coating composition with a 200-mesh filter, a coating film was prepared by spraying on an iron plate substrate. After drying at room temperature for 7 days, the coating film thickness was measured to be 80 μm. The physical properties and salt spray resistance were evaluated, and the results are recorded in Table 1.
[0079] Embodiment 2, 7, 8
[0080] As shown in Tables 1 and 2, the graphene content in the coating film in Example 1, the speed of the disperser for mixing graphene powder and zinc powder during coating preparation, and the speed after adding the epoxy resin main agent were changed. The same operation as in Example 1 was performed to obtain a coating film containing graphene with a low zinc content as shown in Tables 1-2.
[0081] Embodiment 3-6
[0082] The graphene content in the coating film in Example 1 was changed as shown in Table 1, and the same operation as in Example 1 was performed to obtain a coating film containing graphene with a low zinc content as shown in Table 1.
[0083] Examples 9-11
[0084] The zinc content in the coating film in Example 1 was changed as shown in Table 2, and the same operation as in Example 1 was performed to obtain a coating film containing graphene with a low zinc content as shown in Table 2.
[0085] Examples 12-14
[0086] The O / C element composition of the graphene in the coating film in Example 1 was changed as shown in Table 3, and the same operation as in Example 1 was performed to obtain a coating film containing graphene with a low zinc content as shown in Table 3.
[0087] Examples 15-17
[0088] The N / C element composition of the graphene in the coating film in Example 1 was changed as shown in Table 4, and the same operation as in Example 1 was performed to obtain a coating film containing graphene with a low zinc content as shown in Table 4.
[0089] Examples 18-20
[0090] As shown in Table 4, the graphene size and surface treatment parameters in the coating film in Example 1 were changed, and the same operations as in Example 1 were performed to obtain a coating film containing graphene with a low zinc content as shown in Table 4.
[0091] Examples 21-25, 28-30
[0092] As shown in Table 5 and Table 6, the type of surface treatment agent for graphene in the coating film in Example 1 was changed, wherein Example 21 did not use a surface treatment agent, Example 22 used 4-chloroaniline as the surface treatment agent, Example 23 used 2-phenylethylamine hydrochloride as the surface treatment agent, Example 24 used decylaminobenzene hydrochloride as the surface treatment agent, and Example 25 used hexadecylaminobenzene hydrochloride as the surface treatment agent. The surface treatment agent used in Example 28 was benzylamine, the surface treatment agent used in Example 29 was 2-bromo-4-chlorobenzenemethylamine, and the surface treatment agent used in Example 30 was naphthylamine hydrochloride. The same operation as in Example 1 was performed to obtain a coating film containing graphene with a low zinc content as shown in Table 5 and Table 6.
[0093] Examples 26-27
[0094] The resin components in the coating film in Example 1 were changed as shown in Table 5, and the same operation as in Example 1 was performed to obtain a coating film containing graphene with a low zinc content as shown in Table 5.
[0095] Comparative Example 1
[0096] Except that graphene was not added, the same raw materials, preparation conditions and treatment methods as those in Example 1 were used. Due to the lack of graphene, the corrosion potential of the coating was too high and the conductivity was too low, so the corrosion resistance of the coating was poor. The relevant test results are recorded in Table 1.
[0097] Comparative Example 2
[0098] Compared with Example 1, except for increasing the amount of graphene added, the other components, preparation conditions and treatment methods of the coating are the same as those of Example 1. Due to the high content of graphene, the zinc in the coating fails quickly and the salt spray resistance is poor.
[0099] Comparative Example 3
[0100] Compared with Example 1, except for reducing the zinc content to 20wt% of the coating, the other components, preparation conditions and treatment methods of the coating are the same as those of Example 1. Due to the low zinc content, even if the graphene coating is added, it cannot provide a long-term anticorrosion effect. The relevant test results are recorded in Table 2.
[0101] Comparative Example 4
[0102] Compared with Example 1, except for increasing the zinc content to 80wt% of the coating, the other components, preparation conditions and treatment methods of the coating are the same as those of Example 1. For the graphene and dispersion method developed by the present invention for the low zinc content coating, the problem of excessive dispersion of zinc in this comparative example is caused by the excessive zinc content, which leads to a decrease in the anti-corrosion effect. The relevant test results are recorded in Table 2.
[0103] Comparative Example 5
[0104] Compared with Example 1, except for the change of the graphene content to 0.5wt%, the speed of the disperser for mixing graphene powder and zinc powder during coating preparation to 4000rpm, and the speed after adding the epoxy resin main agent to 4000rpm, the other components, preparation conditions and treatment methods of the coating are the same as those of Example 1. Due to the problem of excessive dispersion of zinc and graphene in the present invention, the conductivity of the coating is higher than the limited range of 0.1S / cm. The relevant test results are recorded in Table 3.
[0105] Comparative Examples 6 and 7
[0106] Compared with Example 1, except that graphite (Comparative Example 6) or carbon nanotubes (CNT) (Comparative Example 7) replaces graphene, the other components, preparation conditions and treatment methods of the coating are the same as those of Example 1. It is found that the same content of graphite or CNT cannot replace the addition of graphene. The relevant test results are recorded in Table 3.
[0107] Table 1
[0108]
[0109] Table 2
[0110]
[0111] Table 3
[0112]
[0113] Table 4
[0114] Embodiment 15 Example 16 Embodiment 17 Embodiment 18 Embodiment 19 Embodiment 20 Graphene content (wt%) 0.05 0.05 0.05 0.05 0.05 0.05 Zinc content (wt%) 60 60 60 60 60 60 Resin composition Epoxy resin Epoxy resin Epoxy resin Epoxy resin Epoxy resin Epoxy resin Coating corrosion potential (V) -0.80 -0.90 -0.90 -0.70 -0.85 -0.75 Coating conductivity (S / cm) <![CDATA[1.0×10 -4 ]]> <![CDATA[1.0×10 -2 ]]> <![CDATA[1.0×10 -1 ]]> <![CDATA[2.0×10 -4 ]]> <![CDATA[1.0×10 -4 ]]> <![CDATA[1.0×10 -5 ]]> O / C ratio of graphene 0.11 0.11 0.11 0.11 0.11 0.11 N / C ratio of graphene 0.0005 0.09 0.15 0.01 0.01 0.01 Size in the direction parallel to the graphene layer (μm) 20 20 20 0.05 100 150 Does graphene have surface treatment? have have have have have have Coating preparation speed (rpm) 2500 2500 2500 2500 2500 2500 Reunion none none none none none none Salt spray resistance time (h) 1700 2300 2050 1850 2000 1950 Corrosion width after 100h salt spray test (mm) 0.2 0 0 0.2 0 0.3 Flexibility of coating film (mm) 10 1 1 1 1 1 Impact resistance of coating film (Kg·cm) 50 70 50 65 70 55 Glossiness of coating 9 1.3 5 1.2 7 17 Adhesion of coating film 2 0 1 0 1 2 <![CDATA[Oxygen transmission rate of the coating film (g / m 2 ·h)]]> 37.2 5.3 10.7 7.2 16 29
[0115] Table 5
[0116]
[0117] Table 6
[0118] Embodiment 28 Embodiment 29 Embodiment 30 Graphene content (wt%) 0.05 0.05 0.05 Zinc content (wt%) 60 60 60 Resin composition Epoxy resin Epoxy resin Epoxy resin Coating corrosion potential (V) -0.92 -0.93 -0.90 Coating conductivity (S / cm) <![CDATA[4.0×10 -3 ]]> <![CDATA[3.0×10 -3 ]]> <![CDATA[2.0×10 -3 ]]> O / C ratio of graphene 0.11 0.11 0.11 N / C ratio of graphene 0.01 0.01 0.01 Size in the direction parallel to the graphene layer (μm) 20 20 20 Does graphene have surface treatment? have have have Coating preparation speed (rpm) 2500 2500 2500 Reunion have none none Salt spray resistance time (h) 2530 2550 2500 Corrosion width after 100h salt spray test (mm) 0 0 0 Flexibility of coating film (mm) 1 1 1 Impact resistance of coating film (Kg·cm) 72 71 70 Glossiness of coating 6.5 5.5 5.3 Adhesion of coating film 0 0 0 <![CDATA[Oxygen transmission rate of the coating film (g / m 2 ·h)]]> 0.45 0.47 0.43
Claims
1. A coating film, characterized in that: Contains resin, zinc and graphene, wherein the graphene content in the coating is greater than 0.01wt% and less than 0.5wt%, the zinc content is greater than 30wt% and less than 60wt%, the corrosion potential of the coating is greater than -1.10V and less than -0.70V, and the electrical conductivity is greater than 0.00001S / cm and less than 0.1S / cm.
2. The coating according to claim 1, characterized in that: The atomic ratio of oxygen to carbon in the graphene, namely, the O / C ratio, is measured by X-ray photoelectron spectroscopy to be greater than or equal to 0.001 and less than or equal to 0.
500.
3. The coating according to claim 1, characterized in that: The atomic ratio of nitrogen to carbon in the graphene, namely, the N / C ratio, is measured by X-ray photoelectron spectroscopy to be greater than or equal to 0.001 and less than or equal to 0.
090.
4. The coating according to claim 1, characterized in that: The size of the graphene in a direction parallel to the graphene layer is greater than or equal to 0.10 μm and less than or equal to 100 μm.
5. The coating according to claim 1, characterized in that: The resin includes any one of epoxy resin, polyurethane resin or acrylic resin.
6. The coating film according to any one of claims 1 to 5, characterized in that: The graphene is treated with a surface treatment agent, and the surface treatment agent is the following amino aromatic compound: Wherein, A represents an aromatic group or a heterocyclic aromatic group with a condensation number of 1 to 4, the aromatic group is composed of one of benzene, naphthalene, anthracene, phenanthrene, tetracene, and pyrene, and the heterocyclic aromatic group is composed of one of pyrrole, imidazole, pyridine, triazine, indole, quinoline, and carbazole, and R 1 , R 2 Each independently represents a hydrogen atom, a halogen atom, a carboxyl group, a hydroxyl group, a nitro group, a methyl group, an ethyl group, a propyl group or a butyl group, and R 3 A and N are directly bonded or connected by an alkylene group, wherein the number of carbon atoms of the alkylene group is an integer of 1 to 10, and R 4 , R 5 Each independently represents a hydrogen atom, a methyl group, an ethyl group, a propyl group or a butyl group.
Citation Information
Patent Citations
A kind of two-component graphene anticorrosion coating
CN105086754B
An anti-corrosion coating and its preparation method
CN105440891B